Increased Operative Time for Benign Cranial Nerve Tumor Resection Correlates with Increased Morbidity Postoperatively - Murphy, Meghan; Gilder, Hannah; McCutcheon, Brandon A.; Kerezoudis, Panagiotis; Rinaldo, Lorenzo; Shepherd, Daniel; Maloney, Patrick; Snyder, Kendall; Carlson, Matthew L.; Carter, Bob S.; Bydon, Mohamad; Van Gompel, Jamie J.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objectives Operative time, previously identified as a risk factor for postoperative morbidity, is examined in patients undergoing benign cranial nerve tumor resection.Design/Setting/Participants This retrospective cohort analysis included patients enrolled in the ACS-NSQIP registry from 2007 through 2013 with a diagnosis of a benign cranial nerve neoplasm.Main Outcome Measures Primary outcomes included postoperative morbidity and mortality. Readmission and reoperation served as secondary outcomes.Results A total of 565 patients were identified. Mean (median) operative time was 398 (370) minutes. The 30-day complication, readmission, and return to the operating room rates were 9.9%, 9.9%, and 7.3%, respectively, on unadjusted analyses. CSF leak requiring reoperation or readmission occurred at a rate of 3.1%. On multivariable regression analysis, operations greater than 413 minutes were associated with an increased odds of overall complication (OR 4.26, 95% CI 2.08–8.72), return to the operating room (OR 2.65, 95% CI 1.23–5.67), and increased length of stay(1.6 days, 95% CI 0.94–2.23 days). Each additional minute of operative time was associated with an increased odds of overall complication (OR 1.004, 95% CI 1.002–1.006) and increased length of stay (0.006 days, 95% CI 0.004–0.008).Conclusion Increased operative time in patients undergoing surgical resection of a benign cranial nerve neoplasm was associated with an increased rate of complications.
Keywords: acoustic neuroma; vestibular schwannoma; skull base; operative time; complications; national surgical quality improvement program